Light and the distribution of time. (26th May 2015) - Calonico, D.; Inguscio, M.; Levi, F.
Abstract: Light allows to time travel: light from the Universe offers the possibility to look back to its ancestral epochs, at the very first moments. Nowadays light is also a carrier that allows time to travel, bringing atomic clocks references with the most advanced precision. The frontier of timekeeping and time transfer using light paves the way to unprecedented applications in science and metrology. Light is fundamental in the present effort to redefine the unit of time, to improve our knowledge of fundamental physics laws, geodesy, radioastronomy. Light could be also a new mean to investigate dark matter in the known Universe and possibly to detect gravitational waves.